Blood-brain barrier dysfunction can contribute to pharmacoresistance of seizures - Salar, Seda; Maslarova, Anna; Lippmann, Kristina; Nichtweiss, Julia; Weissberg, Itai; Sheintuch, Liron; Kunz, Wolfram S.; Shorer, Zamir; Friedman, Alon; Heinemann, Uwe (Epilepsia, 2014)
Summary Objective We tested the hypothesis that interstitial albumin can contribute to pharmacoresistance, which is common among patients with focal epilepsies. These patients often present with an open blood-brain barrier (BBB), resulting in diffusion of drug-binding albumin into the brain interstitial space. Methods Seizure-like events (SLEs) induced by 100 μm 4-aminopyridine (4-AP) were monitored using extracellular field potential recordings from acute rat entorhinal cortex-hippocampus slices. Effects of standard antiepileptic drugs (phenytoin, valproic acid, carbamazepine, and phenobarbital) were studied in the presence of albumin applied acutely or by intraventricular injection. Unbound antiepileptic drugs (AEDs) were detected by ultrafiltration and high-performance liquid chromatography (HPLC). Results Contrary to the absence of albumin, conventional AEDs failed to suppress SLEs in the rat entorhinal cortex in the presence of albumin. This effect was partially caused by buffering of phenytoin and carbamazepine (CBZ) by albumin. Increasing CBZ concentration from 50 μm to 100 μm resulted in block of SLEs. In slices obtained from animals that were pretreated with intraventricular albumin application 24 h prior to experiment, CBZ suppressed SLEs similar to control slices. We also found that application of serum-like electrolytes transformed SLEs into late recurrent discharges (LRDs), which were no longer responding to CBZ. Significance A dysfunctional BBB with acute extravasation of serum albumin into the brain's interstitial space could contribute to pharmacoresistance. In such instances, choice of an AED with low albumin binding affinity may help in seizure control. © 2014 International League Against Epilepsy.
Created from Fastlane, Scopus look-up
Keywords: 4-Aminopyridine; Albumin; BBB disruption; Entorhinal Cortex; Pharmacoresistance; Rats